Distributed Simulations of Automotive Related Real-Time Systems Using the High Level Architecture Standard - Jakobson, Ola (My University, 2012)
In this project, the standard High Level Architecture (HLA) has been used in the area of automotive related distributed simulation systems. The purpose was to evaluate the possibility to use HLA for verification of such systems. This has been performed by building and evaluating three different prototypes. The simulation members, federates, of the prototypes had real-time requirements with guidelines of being able to exchange data corresponding to an amount of 10 000 bits, within 10 ms and with an update period of 10 ms. The first prototype involves federates transferring data between two Hardware-In-the-Loop (HIL)-simulators from dSPACE. The second and third involve federates executing in MATLAB and Simulink, respectively. The results of the prototypes indicate that it most likely is possible to use HLA in such simulation systems. However, the amount of work needed to make everything function varies from case to case and sometimes tend to be relatively high. Regarding the distributed data being sent between federates, the wanted way would be to pack data into containers of small size. Doing this would result in the federates being able to only receive the data they are actually interested in. However, handling a large amount of small size containers with data within a short time period is very computationally demanding. Thus,in order to succeed with the MATLAB and Simulink prototypes with respect to the requirements, data had to be packed into larger containers. Doing that made it possible to transfer data amounts many times greater than the stated data criterion. Another use-case that might be even more promising regarding HLA and the automotive industry came up during the thesis work. It involves running distributed Simulink models offline (without the real-time requirements) executed time-synchronized, with help of HLA.
Keywords: Människa-datorinteraktion (interaktionsdesign); Informations- och kommunikationsteknik; Human Computer Interaction; Information & Communication Technology